Tonga : Early Warning Systems Needs Assessment - World Bank (World Bank, Washington, DC, 2020)
This document provides an overview of needs and gaps in regard to early warning and response capabilities in Tonga. It consolidates information gathered in: (i) August 2014 during an early warning system (EWS) needs assessment to inform the development of the World Bank’s Pacific resilience program (PREP); and (ii) August 2016 from discussions with key stakeholders (government bodies and development partners) about EWS activities currently underway or recently completed. Using this information this document identifies the needs for future EWS activities which remain unfunded. A number of activities supporting EWS have been undertaken in Tonga in recent years. This report provides a matrix of activities against the key areas of EWS. By providing a clear outline of the current state of play for EWS in Tonga and identified outstanding needs it is hoped this document will support discussions about future investments in this sector.